Species diversity and distribution of marine wood borers in Blungei Bay Mangrove area, Lundu Kuching Sarawak - Demas, Yahya @ Demas Lai. (Universiti Malaysia Sarawak (UNIMAS), 2004)
A study on the diversity and distribution of marine wood borers was conducted in Blungei Bay, Lundu, Sarawak. A total of 26 species of organisms including non-boring related organims was sampled. Only 12 species of marine wood borers which were categorized under the bivalves were found during the study. Teredo sp. number was the most abundant marine borer at Blungei Bay mangrove. Bactrophorus thoracites, the shipworm and Neanthes sp., the polychaete were the two species found at all sampling site except at higher intertidal zone, near the estuary environment. Correlation analysis shows that salinity influence the number of species occurences.